2014
DOI: 10.1002/pnp.344
|View full text |Cite
|
Sign up to set email alerts
|

Tackling psychopathy: a necessary competency in leadership development?

Abstract: In the second of his two reflections on the Francis Report, Dr de Silva discusses the culture of workplace bullying and the role of a leader in addressing associated psychopathy in the National Health Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Echoing the report from New Zealand, this details how lives were needlessly lost, through poor management, in a major hospital of the UK's National Health Service (NHS). Since then one retired senior doctor, with specific reference to the NHS, has suggested that managers should be taught how to deal with psychopaths in the workplace, to help prevent further ethical lapses (de Silva, 2014).…”
Section: The Effects Of Organisational Psychopaths On Organisationsmentioning
confidence: 99%
“…Echoing the report from New Zealand, this details how lives were needlessly lost, through poor management, in a major hospital of the UK's National Health Service (NHS). Since then one retired senior doctor, with specific reference to the NHS, has suggested that managers should be taught how to deal with psychopaths in the workplace, to help prevent further ethical lapses (de Silva, 2014).…”
Section: The Effects Of Organisational Psychopaths On Organisationsmentioning
confidence: 99%
“…Unfortunately, as we outline in this section of our study, once a workplace monster has been hired, the first an organisation is likely to know of their presence is after the negative consequences of their conduct manifest. Despite being recommended (de Silva, ), few organisations undertake pre‐employment screening for dark triad traits such as psychopathy. Thus, no lead indicators or early warning signs exist, leaving organisations to rely on detecting monster presence via various lag indicators, if at all.…”
Section: Signs Of Monsterly Presence and Activitymentioning
confidence: 99%
“…Interestingly, in Wearne v State of Victoria [2017] VSC 25 (refer Table ), the Judge criticised what they referred to as the noticeable inaction by the HR function, explicitly referring to its failure to intervene in a known escalating conflict, and further declaring the absence of a formal complaint or grievance was not a reliable defence in the context. Additionally, as mentioned earlier, barely any organisations undertake any proactive measures such as pre‐employment screening for workplace monster personalities, despite it being recommended (de Silva, ).…”
Section: Ways Forwardmentioning
confidence: 99%
“…In line with this viewpoint, in commenting on the NHS a retired medical consultant has recently written that psychopaths within the service need to be managed or screened for in order to minimise the damage they do, especially in relation to bullying. de Silva observes that psychopathy and bullying are correlated and that psychopaths therefore need to be screened for and/or managed in the NHS to minimise their destructiveness (de Silva, 2014). de Silva suggests that the culture of endemic bullying described in the 2013 Francis Report on the Mid Staffordshire NHS Foundation Trust may exist across the whole NHS and is a barrier to the delivery of good quality care to patients.…”
Section: Possibly Systemic Psychopathy In the Nhsmentioning
confidence: 99%